Perkawinan Antara Warga Negara Indonesia dan Warga Negara Asing dalam Melindungi Hak Perempuan dan Anak (Implementasi UU Nomor 12 TAHUN 2006 Tentang Kewarganegaraan RI) - Midia, Fredy Gandhi; Apriyana, Dian; Duta, Achmad Arya (Institut Agama Islam Negeri Metro, 2023)
Mixed marriage is a marriage between people of different nationalities, one of whom is an Indonesian citizen. In this regard, in 2006 the Citizenship Law of the Republic of Indonesia No. 12 which aims to protect women who marry foreigners as a result of mixed marriages and their children. Legal issues can arise in mixed marriages, including issues related to the nationality status of either husband or wife and the citizenship status of the children. The purpose of this writing is to study and understand Law no. 12 of 2006 in defending the rights of women and children in mixed marriages. The data collection method is in the form of document study research derived from secondary data which is then analyzed using a qualitative descriptive method. The results of the discussion show that Law no. 12 of 2006 in essence prohibits discrimination and protects the rights of wives and children of Indonesian citizens who are intermarried and foreigners in the Republic of Indonesia.